Multiple charge density wave phases of monolayer VSe2 manifested by graphene substrates. (18th June 2021) - Duvjir, Ganbat; Choi, Byoung Ki; Thi Ly, Trinh; Lam, Nguyen Huu; Jang, Kyuha; Dung, Dang Duc; Chang, Young Jun; Kim, Jungdae
Abstract: A combined study of scanning tunneling microscopy (STM) and angle-resolved photoemission spectroscopy (ARPES) is conducted to understand the multiple charge density wave (CDW) phases of monolayer (ML) VSe2 films manifested by graphene substrates. Submonolayer (∼0.8 ML) VSe2 films are prepared on two different substrates of single-layer graphene (SLG) and bi-layer graphene (BLG) on a 6H-SiC(0001). We find that ML VSe2 films are less coupled to the SLG substrate compared to that of ML VSe2 /BLG. Then, ML VSe2 grown on SLG and BLG substrates reveals a very different topography in STM. While ML VSe2 /BLG shows one unidirectional modulation of √3 × 2 and √3 × √7 CDW in topography, ML VSe2 /SLG presents a clear modulation of 4 × 1 CDW interfering with √3 × 2 and √3 × √7 CDW which has not been previously observed. We explicitly show that the reciprocal vector of 4 × 1 CDW fits perfectly into the long parallel sections of cigar-shaped Fermi surfaces near the M point in ML VSe2, satisfying Fermi surface nesting. Since bulk VSe2 is also well-known for the 4 × 4 × 3 CDW formed by Fermi surface nesting, the 4 × 1 CDW in ML VSe2 /SLG is attributed to the planar projection of 4 × 4 × 3 CDW in bulk. Our result clarifies the nature of the 4 × 1 CDW in ML VSe2 system and is a good example demonstrating the essential role of substrates in two-dimensional transition metal dichalcogenides.